(untitled) (Journal of Informatics Education and Research, 2024)
The effect of overconfidence bias on investing decision-making procedures and results is investigated in this paper. Financial markets and personal investment performance can be much influenced by overconfidence, a cognitive bias whereby people overestimate their knowledge, skills, or chances of success. This research explores how overconfidence shows in several spheres of investment behavior, including excessive trading, risk perception, and portfolio diversification, by means of a thorough literature review and empirical analysis. Using a mixed-methods approach, the study combines qualitative insights from semi-structured interviews with 50 professional fund managers with quantitative analysis of trade data from a 500-retail investor sample over a three-year period. Overconfident investors, according to results, trade more often, have less diversified portfolios, and undervalue investing risks, which results in worse than ideal profits relative to their less confident colleagues. The research ends with addressing the ramifications of these results for individual investors, financial advisers, and legislators, so suggesting ways to reduce the negative consequences of overconfidence bias in investing decision-making.